Educational assortative mating as a determinant of changing household income inequality: A 22-country study - Diederik Boertien; I\~naki Permanyer (Luxembourg Income Study (LIS), 2017)
In a search for determinants of societal levels of income inequality, scholars have suggested that homogamy within marriages and cohabiting relationships is a potentially important driver of inequality. If resourceful persons form couples together, and individuals without resources partner each other too, inequality between households is expected to be higher compared to the situation where partnerships are formed across groups. Education is an important socioeconomic marker on which partners select each other. The results of this paper, however, show that changes over time in educational homogamy are unlikely to have contributed to changes in income inequality. This finding is based on counterfactual simulations performed for 21 European countries and the United States using data from the Luxembourg Income Studies. In a second stage of the analysis we examine why changes in educational assortative mating mattered relatively little for changes in income inequality. A major hypothesis proposed in earlier research is that changes in educational homogamy have not been large enough to affect income inequality. However, based on simulations where educational homogamy are minimized and maximized, we document that even extreme changes in the association between partners' levels of education would not lead to major increases in income inequality.
Keywords: 330; Ehe; Bildungsniveau; Haushaltseinkommen; Einkommensverteilung; USA; Norwegen